A method for reducing sulfur content in positive electrode material precursor
By adding graphene to the co-precipitation slurry of the nickel-cobalt-manganese ternary positive electrode material precursor, adsorbing sulfate ions, the problem of excessive sulfur content in the prior art is solved, and the preparation of a positive electrode material precursor with low sulfur content is realized, which improves battery performance and reduces production costs.
Patent Information
- Application Number
- CN202411960829.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
AI Technical Summary
In the prior art, when preparing the nickel-cobalt-manganese ternary positive electrode material precursor for lithium-ion batteries, it is difficult to effectively remove sulfate ions, resulting in the sulfur content in the product exceeding the standard, affecting the battery performance and increasing the washing cost.
Graphene is added to the co-precipitation slurry prepared using metal sulfates, and the high specific surface area and abundant active sites of graphene are used to adsorb sulfate ions in the precursor of the positive electrode material through electrostatic interaction and coordination, thereby reducing the sulfur content.
Through the adsorption of graphene, the sulfur content in the precursor of the positive electrode material is significantly reduced to reach no more than 600ppm, improving battery performance and reducing production costs.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a method for reducing the sulfur content in a positive electrode material precursor. Background Art
[0002] Nickel-cobalt-manganese ternary positive electrode material precursor is a commonly used material in lithium-ion batteries and is used to manufacture high-performance lithium-ion batteries. Its preparation process is dissolution-reaction-washing-drying-packaging. First, a mixed solution of nickel-cobalt-manganese sulfate with a certain concentration is prepared, and then added to the reactor at the same time with nickel liquid alkali and ammonia water for coprecipitation reaction. Because the nickel-cobalt-manganese metal salt used in its preparation process is sulfate, a large amount of sulfate ions are attached to the inside and surface of the material during the preparation of the ternary precursor. The commonly used desulfurization method is to use hot alkaline hot water to wash the material multiple times, but it can only remove the sulfur adsorbed on the surface of the precursor, and the sulfur embedded in the material is always difficult to wash away, resulting in the S content in the products produced by this process generally exceeding the standard. This not only increases the washing cost, but also has a great impact on the performance of the final battery. Summary of the invention
[0003] The purpose of the present invention is to overcome the defects of the prior art and provide a method for reducing the sulfur content in a positive electrode material precursor.
[0004] The present invention solves the technical problem by adopting the following technical solutions.
[0005] The present invention provides a method for reducing the sulfur content in a positive electrode material precursor, which comprises: adding graphene to a coprecipitation slurry prepared using metal sulfate, and using the graphene to adsorb sulfate ions in the positive electrode material precursor, thereby reducing the sulfur content in the positive electrode material precursor.
[0006] The present invention also provides a positive electrode material precursor prepared by the above method, wherein the sulfur content in the positive electrode material precursor is not higher than 600 ppm.
[0007] The present invention has the following beneficial effects:
[0008] The present invention provides a method for reducing the sulfur content in a positive electrode material precursor, which comprises: adding graphene to a coprecipitation slurry prepared using metal sulfate, and using the graphene to adsorb sulfate ions in the positive electrode material precursor, thereby reducing the sulfur content in the positive electrode material precursor. The present invention utilizes the characteristics of high specific surface area and abundant active sites of graphene materials, and can adsorb sulfate ions in the coprecipitation slurry through electrostatic interaction and coordination, thereby reducing the sulfur content in the positive electrode material precursor. DETAILED DESCRIPTION
[0009] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0010] A method for reducing the sulfur content in a positive electrode material precursor provided by an embodiment of the present invention is described in detail below.
[0011] In a first aspect, an embodiment of the present invention provides a method for reducing the sulfur content in a positive electrode material precursor, comprising: adding graphene to a co-precipitation slurry prepared using metal sulfate, and using the graphene to adsorb sulfate ions in the positive electrode material precursor, thereby reducing the sulfur content in the positive electrode material precursor.
[0012] The embodiment of the present invention provides a method for reducing the sulfur content in a positive electrode material precursor, which includes: adding graphene to a coprecipitation slurry prepared using metal sulfate, wherein the graphene material has good adsorption, a large surface area and abundant active sites, and these characteristics make it an excellent adsorbent. Graphene is added to the coprecipitation slurry prepared using metal sulfate, and by utilizing the high specific surface area and abundant active site characteristics of the graphene material, sulfate ions can be adsorbed in the solution through electrostatic interaction and coordination, thereby reducing the sulfur content in the positive electrode material precursor.
[0013] In some optional embodiments, it includes: preparing a co-precipitation slurry using sulfate, then aging the co-precipitation slurry and adding a graphene solution thereto for stirring, and using graphene to adsorb sulfate ions in the positive electrode material precursor, thereby reducing the sulfur content in the positive electrode material precursor.
[0014] An embodiment of the present invention provides a method for reducing the sulfur content in a positive electrode material precursor, which includes: preparing a co-precipitation slurry using sulfate, then aging the co-precipitation slurry and adding a graphene solution thereto for stirring, adding the graphene solution to the co-precipitation slurry, and the graphene in the graphene solution is more fully dissolved and better dispersed, which is conducive to the adsorption of sulfur impurities in the positive electrode material precursor.
[0015] In some optional embodiments, the graphene concentration in the co-precipitation slurry is 0.05 mg / L-50 mg / L.
[0016] In some optional embodiments, the method further comprises: after the stirring is completed, washing, drying, sieving and deironing the coprecipitated slurry containing the graphene solution with a hot alkaline solution and hot water in sequence to obtain a positive electrode material precursor with a low sulfur content.
[0017] The embodiment of the present invention provides a method for reducing the sulfur content in a positive electrode material precursor. By utilizing the high specific surface area and rich active sites of graphene materials, sulfate ions can be adsorbed in the co-precipitation slurry through electrostatic interaction and coordination. The desulfurization effect of hot alkali can be used to efficiently remove the impurity sulfur in the precursor, and hot water can be used to remove the residual impurities, thereby obtaining a ternary positive electrode material precursor with a low sulfur content.
[0018] In some optional embodiments, the hot alkali includes at least one of lithium hydroxide, sodium hydroxide, and potassium hydroxide, the concentration of the hot alkali solution is 0.5-1.5 mol / L, the temperature is 70±5°C, and the temperature of the hot water is 70±5°C.
[0019] In some optional embodiments, the preparation of the coprecipitation slurry comprises the following steps: under the protection of an inert gas, a mixed metal sulfate solution, a precipitant and a complexing agent are simultaneously introduced into a base liquid to carry out a coprecipitation reaction to obtain a coprecipitation slurry.
[0020] In some optional embodiments, the preparation of the base liquid includes the following steps: adding pure water to the reactor, introducing inert gas to replace the air, and after the air in the reactor is replaced, stirring and heating are turned on. After the temperature reaches the required temperature, a complexing agent is added to the pure water, and an alkali solution is used to adjust the pH value of the solution in the reactor to the target value, thereby obtaining the base liquid; wherein: the ammonia value of the base liquid is 2-16g / L, the pH value is 11.3-12.3, and the temperature is 40-80°C.
[0021] In some optional embodiments, the precipitant includes sodium hydroxide; the complexing agent includes at least one of ammonia water, EDTA, citric acid, tartaric acid, and oxalic acid.
[0022] In some optional embodiments, during the co-precipitation reaction, the reaction system temperature is controlled to be 40-80°C, the ammonia value is 3-16g / L, the pH value is 11.3-12.3, the stirring rate is 200-500r / min, the flow rate of the mixed metal sulfate solution is 100-800L / h, and the feeding is stopped after the reaction kettle slurry particle size reaches the target range.
[0023] In a second aspect, an embodiment of the present invention further provides a positive electrode material precursor prepared by the above method, wherein the sulfur content in the positive electrode material precursor is not higher than 600 ppm.
[0024] The present invention will be further described below in conjunction with the embodiments.
[0025] A method for reducing the sulfur content in a positive electrode material precursor comprises the following steps:
[0026] Step 1: Use nickel-cobalt-manganese salt crystals to prepare 1.8-2.2 mol / L ternary liquid, and simultaneously prepare 5-12 mol / L liquid alkali solution, with ammonia concentration of 15-25%.
[0027] Step 2: Add 3-7m 3 Pure water is heated to 40-80℃, and ammonia water and liquid caustic soda are added to adjust the ammonia value to 2-16g / L and the pH value to 11.3-12.3. When preparing the base solution, 1-10m 3 / h of nitrogen for 4h.
[0028] Step 3: After the base solution is prepared, nickel-cobalt-manganese salt, ammonia water and liquid alkali are added simultaneously through a metering pump, the reaction system temperature is controlled at 40-80°C, the ammonia value is 3-16g / L, the pH value is 11.3-12.3, the flow rate of the nickel-cobalt-manganese metal salt solution is 100-800L / h, and the reactor is stirred at 200-500r / min. The reaction is stopped when the particle size of the reactor slurry reaches the target range.
[0029] Step 4: discharge the materials in the reactor into the aging tank, and add a certain amount of graphene solution into the aging tank to control the concentration of the graphene solution in the aging tank to be 0.01-50 mg / L. After stirring for 2 hours, the precursor slurry containing the graphene solution is pumped into a centrifuge, and washed and dried using hot alkali and hot water respectively.
[0030] Step 5: Finally, after drying, screening, iron removal and packaging, a low-sulfur ternary cathode material precursor is produced. The molecular formula is: Ni x Co y Mn 1-x-y (OH)2, where 0.33≤x≤0.9, 0.05≤y≤0.33, 0.05≤1-xy≤0.33.
[0031] Example 1
[0032] Step 1: Prepare a ternary solution of nickel, cobalt and manganese with a ratio of 8:1:1 and a concentration of 2 mol / L. Use ultrasonic dispersion method to prepare a 20 g / L graphene solution.
[0033] Step 2: Add 3m 3 Pure water was heated to 55°C, the stirring blade inside the reactor was operated at a speed of 300r / min, and then 30% of liquid alkali solution was added to adjust the pH value to 11.80±0.05, and 16% of ammonia solution was added to adjust the bottom liquid ammonia value to 8±0.5g / L, and 5m 3 / h of nitrogen for nitrogen protection. Then add 2.0mol / L nickel-cobalt-manganese solution at a flow rate of 200L / h, control the ammonia value of the reactor system to 8±0.5g / L and the pH to 11.60-11.90 through liquid alkali and ammonia water, and control the stirring speed to 300r / min and the reaction temperature to 55℃ for continuous reaction.
[0034] Step 3: When the particle size of the slurry in the reactor reaches 9.5-10.5 μm, stop feeding and discharge the material into the aging tank. Add graphene solution into the aging tank, control the concentration of graphene solution in the aging tank to 0.5 mg / L, stir for 2 hours, and then pump the material in the aging tank into a centrifuge using a 1.0 m 3 1.0 mol / L of 70°C liquid caustic soda, 1.5 m 3 Wash and dry with 70℃ hot water.
[0035] Step 4: The washed and dried material is dried, sieved, iron removed, and packaged to obtain Ni with low sulfur content. 0.8 Co 0.1 Mn 0.1 (OH)2 ternary cathode material precursor.
[0036] Example 2
[0037] Step 1: Prepare a ternary solution of nickel, cobalt and manganese with a ratio of 6:2:2 and a concentration of 2 mol / L. Use ultrasonic dispersion method to prepare a 20 g / L graphene solution.
[0038] Step 2: Add 3m 3 Pure water was heated to 60°C, the stirring blade inside the reactor was operated at a speed of 300r / min, and then 30% of liquid alkali solution was added to adjust the pH value to 11.80-12.00, and 16% of ammonia solution was added to adjust the bottom liquid ammonia value to 6±0.5g / L, and 5m 3 / h of nitrogen for nitrogen protection. Then add 2.0mol / L nickel-cobalt-manganese solution at a flow rate of 300L / h, control the ammonia value of the reactor system to 6±0.5g / L and the pH to 11.50-11.90 through liquid alkali and ammonia water, and control the stirring speed to 300r / min and the reaction temperature to 60℃ for continuous reaction.
[0039] Step 3: When the particle size of the slurry in the reactor reaches 3.0-4.0 μm, stop feeding and discharge the material into the aging tank. Add graphene solution into the aging tank, control the concentration of graphene solution in the aging tank to 0.5 mg / L, stir for 2 hours, and then pump the material in the aging tank into a centrifuge using a 1.0 m 3 1.0 mol / L of 70°C liquid caustic soda, 1.5 m 3 Wash and dry with 70℃ hot water.
[0040] Step 4: The washed and dried material is dried, sieved, iron removed, and packaged to obtain Ni with low sulfur content. 0.6 Co 0.2 Mn 0.2 (OH)2 ternary cathode material precursor.
[0041] Example 3
[0042] Step 1: Prepare a ternary solution of nickel, cobalt and manganese with a ratio of 5:2:3 and a concentration of 2 mol / L. Use ultrasonic dispersion method to prepare a 20 g / L graphene solution.
[0043] Step 2: Add 4m 3 Pure water was heated to 55°C, the stirring blade inside the reactor was operated at a speed of 300r / min, and then 30% of liquid alkali solution was added to adjust the pH value to 11.80±0.05, and 16% of ammonia solution was added to adjust the bottom liquid ammonia value to 6±0.5g / L, and 5m 3 / h of nitrogen for nitrogen protection. Then add 2.0mol / L nickel-cobalt-manganese solution at a flow rate of 250L / h, control the ammonia value of the reactor system to 6±0.5g / L and the pH to 11.60-11.80 through liquid alkali and ammonia water, and control the stirring speed to 300r / min and the reaction temperature to 55±0.5℃ for continuous reaction.
[0044] Step 3: When the particle size of the slurry in the reactor reaches 3.5-4.5 μm, stop feeding and discharge the material into the aging tank. Add graphene solution into the aging tank, control the concentration of graphene solution in the aging tank to 0.4 mg / L, stir for 2 hours, and then pump the material in the aging tank into a centrifuge using a 1.0 m 3 1.0 mol / L of 70°C liquid caustic soda, 1.5 m 3 Wash and dry with 70℃ hot water.
[0045] Step 4: The washed and dried material is dried, sieved, iron removed, and packaged to obtain Ni with low sulfur content. 0.5 Co 0.2 Mn 0.3 (OH)2 ternary cathode material precursor.
[0046] Example 4
[0047] Step 1: Prepare a ternary solution of nickel, cobalt and manganese with a ratio of 5:2:3 and a concentration of 2 mol / L. Use ultrasonic dispersion method to prepare a 20 g / L graphene solution.
[0048] Step 2: Add 4m 3Pure water was heated to 55°C, the stirring blade inside the reactor was operated at a speed of 300r / min, and then 30% of liquid alkali solution was added to adjust the pH value to 11.80±0.05, and 16% of ammonia solution was added to adjust the bottom liquid ammonia value to 6±0.5g / L, and 5m 3 / h of nitrogen for nitrogen protection. Then add 2.0mol / L nickel-cobalt-manganese solution at a flow rate of 250L / h, control the ammonia value of the reactor system to 6±0.5g / L and the pH to 11.60-11.80 through liquid alkali and ammonia water, and control the stirring speed to 300r / min and the reaction temperature to 55±0.5℃ for continuous reaction.
[0049] Step 3: When the particle size of the slurry in the reactor reaches 3.5-4.5 μm, stop feeding and discharge the material into the aging tank. Add graphene solution into the aging tank, control the concentration of graphene solution in the aging tank to 0.8 mg / L, stir for 2 hours, and then pump the material in the aging tank into a centrifuge using a 1.0 m 3 1.0 mol / L of 70°C liquid caustic soda, 1.5 m 3 Wash and dry with 70℃ hot water.
[0050] Step 4: The washed and dried material is dried, sieved, iron removed, and packaged to obtain Ni with low sulfur content. 0.5 Co 0.2 Mn 0.3 (OH)2 ternary cathode material precursor.
[0051] Comparative Example 1
[0052] The steps are the same as those in Example 1, except that no graphene solution is added.
[0053] Comparative Example 2
[0054] The steps are the same as those in Example 2, except that no graphene solution is added.
[0055] Comparative Example 3
[0056] The steps are the same as those in Example 3, except that no graphene solution is added.
[0057] Comparative Example 4
[0058] The steps are the same as those in Comparative Example 3, except that the amounts of washing alkali and water are changed.
[0059] Step 1: Prepare a nickel-cobalt-manganese ternary solution with a ratio of 5:2:3 and a concentration of 2 mol / L.
[0060] Step 2: Add 4m 3Pure water was heated to 55°C, the stirring blade inside the reactor was operated at a speed of 300r / min, and then 30% of liquid alkali solution was added to adjust the pH to 11.80±0.05, and 16% of ammonia solution was added to adjust the bottom liquid ammonia value to 6±0.5g / L, and 5m 3 / h of nitrogen for nitrogen protection. Then add 2.0mol / L nickel-cobalt-manganese solution at a flow rate of 250L / h, control the ammonia value of the reactor system to 6±0.5g / L and the pH to 11.60-11.80 through liquid alkali and ammonia water, and control the stirring speed to 300r / min and the reaction temperature to 55±0.5℃ for continuous reaction.
[0061] Step 3: When the particle size of the slurry in the reactor reaches 3.5-4.5 μm, stop feeding and discharge the material into the aging tank. After stirring for 2 hours, pump the material in the aging tank into a centrifuge using a 1.0 m 3 2.0 mol / L of 70°C liquid caustic soda, 2.5 m 3 Wash and dry with 70℃ hot water.
[0062] Step 4: The washed and dried material is dried, sieved, iron removed, and packaged to obtain Ni 0.5 Co 0.2 Mn 0.3 (OH)2 ternary cathode material precursor.
[0063] The following table shows the Na content and S content of the positive electrode material precursors prepared in the examples and comparative examples.
[0064] Serial number Cathode material precursor Na(ppm) S(ppm) 1 Example 1 41.1 453.2 2 Example 2 50.2 434.7 3 Example 3 62.0 421.6 4 Example 4 63.2 418.7 5 Comparative Example 1 41.4 721.7 6 Comparative Example 2 51.9 699.4 7 Comparative Example 3 61.2 733.1 8 Comparative Example 4 59.7 725.4
[0065] It can be seen from the above table that compared with the Na content and S content of the products in Examples 1 to 3, the products in Comparative Examples 1 to 4 did not add graphene solution during the preparation process, and the sulfur content of the products in Comparative Examples 1 to 4 was significantly higher than that in Examples 1 to 4. In addition, Comparative Example 4 is based on Comparative Example 3, and the amount of hot alkali and hot water is further increased, but the decrease in the sulfur content in the positive electrode material precursor is small, indicating that the sulfur in the positive electrode material precursor is not removed by hot alkali and hot water, and is mainly removed by adsorption of graphene and then washing.
[0066] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for reducing the sulfur content in a positive electrode material precursor, characterized in that: The method comprises: adding graphene to a coprecipitation slurry prepared by using metal sulfate, and utilizing the graphene to adsorb sulfate ions in a positive electrode material precursor, thereby reducing the sulfur content in the positive electrode material precursor.
2. The method according to claim 1, characterized in that It includes: A coprecipitation slurry is prepared using sulfate, and then the coprecipitation slurry is aged and a graphene solution is added thereto for stirring, and the graphene is used to adsorb sulfate ions in the positive electrode material precursor, thereby reducing the sulfur content in the positive electrode material precursor.
3. The method according to claim 1 or 2, characterized in that: The graphene concentration in the coprecipitation slurry is 0.05 mg / L-50 mg / L.
4. The method according to claim 1 or 2, characterized in that: Also includes: After the stirring is completed, the co-precipitation slurry containing the graphene solution is washed, dried, sieved and deironed using a hot alkaline solution and hot water in sequence to obtain a positive electrode material precursor with a low sulfur content.
5. The method according to claim 4, characterized in that The hot alkali includes at least one of lithium hydroxide, sodium hydroxide and potassium hydroxide. The concentration of the hot alkali solution is 0.5-1.5 mol / L, the temperature is 70±5°C, and the temperature of the hot water is 70±5°C.
6. The method according to claim 1 or 2, characterized in that: The preparation of the coprecipitation slurry comprises the following steps: under the protection of inert gas, a mixed metal sulfate solution, a precipitant and a complexing agent are simultaneously introduced into a base liquid to carry out a coprecipitation reaction to obtain the coprecipitation slurry.
7. The method according to claim 6, characterized in that The preparation of the base liquid comprises the following steps: adding pure water to a reaction kettle, introducing an inert gas to replace the air, and after the air in the reaction kettle is completely replaced, stirring and heating are turned on, and after the temperature reaches the required value, a complexing agent is added to the pure water, and an alkali solution is used to adjust the pH value of the solution in the reaction kettle to a target value, thereby obtaining the base liquid; wherein: the ammonia value of the base liquid is 2-16 g / L, the pH value is 11.3-12.3, and the temperature is 40-80°C.
8. The method according to claim 6, characterized in that The precipitant includes sodium hydroxide; the complexing agent includes at least one of ammonia water, EDTA, citric acid, tartaric acid and oxalic acid.
9. The method according to claim 6, characterized in that During the coprecipitation reaction, the temperature of the reaction system is controlled at 40-80°C, the ammonia value is 3-16 g / L, the pH value is 11.3-12.3, the stirring rate is 200-500 r / min, and the feeding is stopped after the particle size of the slurry in the reactor reaches the target range.
10. A positive electrode material precursor prepared according to any one of claims 1 to 9, characterized in that: The sulfur content in the positive electrode material precursor is not higher than 600 ppm.